Innovative strategies for MSME business growth with the business model canvas approach - Abdurrahman Sadikin; Sidrotun Naim; Maisa Azizah Asmara; Trie Hierdawati; Yosep Boari (Institute of Computer Science (IOCS), 2023)
The urgency of the research is the importance of the ability to adapt and innovate in the face of dynamic changes in the business environment to make MSMEs achieve better growth so that this study aims to identify innovative strategies that can support the business growth of vegetarian diet culinary MSMEs with a Business Model Canvas approach. Business Model Canvas is a framework consisting of nine main interrelated elements to plan, develop, and optimize business strategies. Through a case study approach and qualitative research methods, this research explores information from several successful vegetarian diet culinary MSMEs. The results showed that the Business Model Canvas provides flexibility in long-term business planning, increases focus on the important points of business planning, and allows companies to update existing models or elements according to the situation. This research contributes to developing innovative strategies for vegetarian diet culinary MSMEs and can be a practical guide for business owners in achieving sustainable business growth.